Green electronics/green bottom line : environmentally responsible engineering - Goldberg, Lee H.; Middleton, Wendy (Newnes, 2000)
Environmentally safe engineering is one of the hottest and most controversial topics in technical circles. Though many publications offer theory and intellectual discussion of the topic, this book provides practical, hands-on advice including hints and tips from the nation's top engineers. Green Electronics/Green Bottom Line offers practical advice for engineers and managers who want or need to incorporate environmental issues into the design process. The emerging discipline of Design for the Environment (DfE) combines engineering know-how with environmental awareness. Topics include international policy issues such as ISO 14000, materials selection (e.g., for recyclability), manufacturing concerns like no-flux processes, and design issues such as power consumption. Real-world cases show how these elements can be included in everyday designs. Each chapter opens with a topical cartoon and lively story, interview or editorial. The discussion will then move to specific engineering issues and their economic and social context. The last section explores larger possibilities and new directions still to be explored by engineers concerned with education, health, and environmental quality. Contributors include engineers from Motorola, Analog Devices, Dupont, Compaq, Nortel, AMD, and Apple Computer, and academics from universities in the US, Canada, the UK, and Europe, as well as the Rocky Mountain Institute. An everyday guide to environmentally sound electronics design Contributors include top engineers from the biggest electronics manufacturers and most prestigious universities Real-world cases illustrate topics giving concepts the reader can apply immediately.